Bullying of LGBTQ+ children and adolescents in schools: understanding the phenomenon, consequences, and international standards with a focus on the polish context - Stańczykiewicz, Bartłomiej; Senczyszyn, Adrianna (Frontiers in Psychiatry, 2024)
Bullying refers to repetitive, aggressive behavior intended to harm or intimidate others. Cyberbullying extends this aggression to digital platforms, involving harassment via social media, texts, or emails. These forms of bullying are particularly damaging to LGBTQ+ youth, who often face discrimination based on their sexual orientation or gender identity. In the context of LGBTQ+ individuals, bullying and cyberbullying can lead to severe emotional and psychological harm, contributing to higher rates of depression, anxiety, and suicidal ideation. Despite extensive global efforts and campaigns to combat homophobia, LGBTQ+ students continue to face significant challenges, with the situation in Poland being notably severe. The review highlights various forms of bullying, including physical, verbal, and social aggression, and underscores the alarming involvement of school personnel in perpetuating such behaviors. The focus on the Polish context enriches the global discourse on LGBTQ+ rights and highlights the critical need for targeted interventions to support vulnerable youth in regions with prevalent conservative and religious sentiments.